Kamenetsk impact structure on the Ukrainian Shield - Gurov, E.P.; Nikolaenko, N.A.; Shevchuk, H.A.; Yamnichenko, A.Y. (Reports of the National Academy of Sciences of Ukraine, 2018)
The Kamenetsk impact structure is a deeply eroded simple bowl-shaped crater 1.1-1.2 km in diameter, located in the basin of the Ingul river on the southern slope of the Ukrainian Shield. Determination of characteristic features of the shock metamorphism in the rocks of the Kamenetsk structure proves its impact origin and refutes the idea of its endogenous nature. Deep erosion of the crater allows us to assume its ancient, probably, Paleozoic age. The Kamenetsk crater is the eighth impact structure discovered in the Ukrainian Shield.